Sedimentations and emerging cleavages. A social spatial analysis of Rome’s voting patterns during the Second Republic - D’Amelio, Nicola; Mariotti, Claudia (Frontiers in Political Science, 2025)
This study examines the evolution of electoral behavior in Rome during the Second Republic (1993–2024), analyzing the relationship between urban morphology, socio-graphic structures, and political allegiance. Electoral and census data, disaggregated and re-aggregated by toponymic zones instead of administrative units, are visualized through GIS-based cartographic projections. The use of toponymic zones, deeply rooted in Rome’s historical culture, geographical morphology, and social values, enables a finer-grained analysis of electoral alignments that captures lived spatial identities. The findings trace the persistence and transformation of spatial cleavages, highlighting the enduring significance of concentric and radial electoral divisions shaped by infrastructural lines such as the Grande Raccordo Anulare, the Fascia verde, the Aurelian Walls and ancient consular roads. Despite shifts in political supply and voter volatility, certain socio-territorial cleavages remain remarkably stable, reflecting deeper historical, cultural, and socio-economic structures. The study contributes to debates on the resilience of urban territorial belongings and the spatial mediation of political behavior, underlining the importance of historically sedimented spatial units in electoral analysis.